GENDER GAP IN FINANCE - Davronova Madina Baxtiyorovna; Shakhlo Davirova (European Science Publishing, 2025)
The gender gap in finance has a pervasive impact on economic well-being of women. Surely, financially literate woman as well as men are needed to strengthen the economy. The following paper contains analysist of disparity of financial literacy among men and women of various ages and with different backgrounds. Data of the surveys from several countries is collected and analyzed in order to get the full picture of state of gender imbalance in financial matters. This article explores the importance of financial education of women and different possible reasons of lack of financial competence among women. The article examines how well the representatives of two genders know basic financial concepts, at what age are they more likely to make correct financial decisions and how marital status of men and women affect the level of their financial understanding.
Keywords: Financial literacy, financial illiteracy, gender gap in finance, disparity of knowledge, financial decision-making, retirement planning, financial concepts.